The golden mimicry complex uses a wide spectrum of defence to deter a community of predators - Pekár, Stano; Petráková, Lenka; Bulbert, Matthew W; Whiting, Martin J; Herberstein, Marie E (eLife, 2017)
Mimicry complexes typically consist of multiple species that deter predators using similar anti-predatory signals. Mimics in these complexes are assumed to vary in their level of defence from highly defended through to moderately defended, or not defended at all. Here, we report a new multi-order mimicry complex that includes at least 140 different putative mimics from four arthropod orders including ants, wasps, bugs, tree hoppers and spiders. All members of this mimicry complex are characterised by a conspicuous golden body and an ant Gestalt, but vary substantially in their defensive traits. However, they were similarly effective at deterring predators - even mildly defended mimics were rarely eaten by a community of invertebrate and vertebrate predators both in the wild and during staged trials. We propose that despite the predominance of less defended mimics the three predatory guilds avoid the mimics because of the additive influence of the various defensive traits.
Keywords: ecology; Arthropods; mimikry; členovci; Animals; Müllerian mimicry; aposematism; Biological Mimicry; mimetic complex; predation pressure; zvířata